Раннеголоценовый тарпан на территории Северо-Западного Причерноморья - Белан, Н.Г.; Бибикова, В.И. (Вестник зоологии, 1981)
Equus gmelini remains from the Late Mesolythic sites near vil. Mirnoe and vil. Girzhevo of the Odessa Region are described.